Analisis Instrumen Asesmen Unjuk Kerja pada Pembelajaran PJOK di Sekolah Dasar Kota Cirebon - Wahyu Adhi Nugroho; Rivo Panji Yudha; Sri Sundari; Handayani Nila Praja (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2021)
This study aims to analyze the validity and reliability and practicality of the performance assessment instruments in PJOK learning in Cirebon City Elementary Schools. This research uses an R&D development model using Borg and Gall analysis which the researcher modifies into three stages of define design and develop. The results of the content validity test were analyzed using the T Score from all aspects assessed by experts which included aspects of the conformity of aspects with indicators, writing, language, and physical appearance, the ideal percentage value of 91% was included in the criteria Very good and worthy of use. The results of the reliability of performance instruments on a small scale use GENOVA analysis, for passing indicators (0.91), dribbling indicators (0.92). The practicality of the instrument analyzed using the T score obtained an average score of 52.33 and from the T score of each rater I (49), rater II (54), and from rater III a T score (54) was obtained and based on the instrument teacher's assessment performance assessment is classified as practical. In conclusion, the performance assessment instrument in PJOK learning that was developed has met the requirements of validity, reliability and practicality, as an evaluation tool that can be used further by teachers of PJOK SD in Cirebon City. Keywords: Instruments, Performance, PJOK, Valid, Reliable